Sustainability-oriented innovation: a systematic review - Adams, Richard; Jeanrenaud, Sally; Bessant, John; Denyer, David; Overy, Patrick (Wiley, 2015)
This paper is intended as a contribution to the ongoing conceptual development of sustainability-oriented innovation (SOI) and provides initial guidance on becoming and being sustainable. The authors organize and integrate the diverse body of empirical literature relating to SOI and, in doing so, develop a synthesized conceptual framework onto which SOI practices and processes can be mapped. Sustainability-oriented innovation involves making intentional changes to an organization's philosophy and values, as well as to its products, processes or practices to serve the specific purpose of creating and realizing social and environmental value in addition to economic returns. A critical reading of previous literature relating to environmental management and sustainability reveals how little attention has been paid to SOI, and what exists is only partial. In a review of 100 scholarly articles and 27 grey sources drawn from the period of the three Earth Summits (1992, 2002 and 2012), the authors address four specific deficiencies that have given rise to these limitations: the meaning of SOI; how it has been conceptualized; its treatment as a dichotomous phenomenon; and a general failure to reflect more contemporary practices. The authors adopt a framework synthesis approach involving first constructing an initial architecture of the landscape grounded in previous studies, which is subsequently iteratively tested, shaped, refined and reinforced into a model of SOI with data drawn from included studies: so advancing theoretical development in the field of SOI.